B‐cell inhibition by cross‐linking CD79b is superior to B‐cell depletion with anti‐CD20 antibodies in treating murine collagen‐induced arthritis. Issue 3 (28th December 2014) - Brühl, Hilke; Cihak, Josef; Talke, Yvonne; Gomez, Manuel Rodriguez; Hermann, Fabian; Goebel, Nicole; Renner, Kerstin; Plachý, Jiří; Stangassinger, Manfred; Aschermann, Susanne; Nimmerjahn, Falk; Mack, Matthias
<x xml:space="preserve">Abstract</x> Depletion of B cells with the anti‐CD20 antibody rituximab is an established therapy for rheumatoid arthritis. However, rituximab has only moderate efficacy, most likely due to insufficient depletion of B cells in lymphoid organs and expansion of pathogenic B cells. We found that an antibody against mouse CD79b profoundly blocks B‐cell proliferation induced via the B‐cell receptor, CD40, CD180, and chondroitin sulfate, but not via TLR4 or TLR9. Treatment with anti‐CD79b also induces death in resting and activated B cells. B‐cell inhibition is mediated by cross‐linkage of CD79b, but independent of Fc‐receptor engagement. In the model of collagen‐induced arthritis, an antibody against mouse CD20 depletes B cells very efficiently but fails to suppress the humoral immune response against collagen and the development of arthritis. In contrast, the antibody against CD79b, and a deglycosylated variant of this antibody, almost completely inhibits the increase in anti‐collagen antibodies and the development of arthritis. In mice with established arthritis only the fully glycosylated antibody against CD79b is effective. Our data show that targeting B cells via CD79b is much more effective than B‐cell depletion with anti‐CD20 antibodies for therapy of arthritis. These findings may have important implications for treatment of B‐cell–mediated autoimmune diseases.